Symptom Burden and the Efficacy of Psychosocial Interventions in Conservatively Managed End-Stage Kidney Disease: A Systematic Review - Hidayat, Agung Wahyu; Agung, Ratih Arianita; Putri, Chintia Dyah Ayuning (CENDEKIA EKSAKTA, 2026)
Background: Conservative kidney management (CKM) is an increasingly adopted alternative to dialysis for patients with end-stage kidney disease (ESKD), emphasizing quality of life. However, the prevalence of physical and psychological symptoms in this population remains under-evaluated.Objective: This systematic review aims to synthesize the prevalence, severity, and clinical impact of pain and psychological distress (depression, anxiety, and fatigue) in conservatively managed ESKD patients and to evaluate the efficacy of psychosocial interventions.Methods: Following PRISMA guidelines, a comprehensive search of PubMed, Embase, and Scopus was conducted for studies published between January 2015 and July 2025. Methodological quality was appraised using the Newcastle-Ottawa Scale (NOS). Eligible studies included adults ( 18 years) with ESKD managed without dialysis.Results: Seventeen studies () were included. Symptom prevalence was high: pain (38–72%), depression (25–55%), anxiety (19–48%), and fatigue (40–75%). Up to 60% of patients reported moderate-to-severe bone pain, and 70% experienced significant functional impairment due to fatigue. All symptom domains significantly correlated with diminished quality of life (KDQOL scores, ). Psychosocial interventions—including hope therapy, mindfulness-based resilience, and integrated palliative care—consistently demonstrated significant improvements in psychological outcomes ( to ) and emotional well-being.Conclusion: Pain and psychological distress represent a substantial burden in the CKM population. Integrating routine multidisciplinary assessment and evidence-based psychosocial support is essential to optimize patient-centered outcomes in conservative kidney care. Keywords: end-stage kidney disease, conservative kidney management, pain, psychological distress, quality of life,